Effect of selective laser sintering processing parameters on the mechanical properties of peanut shell powder/polyether sulfone composite - Idriss Aboubaker I. B.; Yang Chun-Mei; Li Jian; Zhang Hui; Abdelmagid Alaaeldin A. A. (Reviews on Advanced Materials Science)
Current selective laser sintering (SLS) parts produced from biomass-composites are low-quality due to issues with unsuitable-parameters. This study investigates the influence of various SLS parameters on mechanical properties of peanut shell powder/polyether sulfone composites (PSPC). The aim of this study is to improve the PSPC mechanical strength through the optimization of SLS parameters, i.e., layer-thickness, scan-speed, laser-power, scan-spacing, and preheating-temperature. The study examines how these parameters influence the mechanical properties of PSPC. First, thermophysical-properties of PSPC compounds were analyzed to determine their thermal behavior and optimal sintering-temperature. The mechanical properties were assessed using sensitive testing instruments. Scanning electron microscopy was used to analyze formability-microstructure, particle-distribution, and bonding-strength of PSPC specimens under various parameters. The density and mechanical strengths of PSPC parts correlated-directly with laser-power and preheating-temperature, while precision and surface-roughness showed an inverse-correlation. Conversely, mechanical strengths and density inversely-correlated with layer-thickness, scanning-speed, and scan-spacing, whereas precision and surface-roughness displayed a direct-correlation with these parameters. PSPC offers cost-effective, eco-friendly parts, reducing pollution from peanut-waste disposal. Optimizing SLS parameters produced parts with better strengths, dimension precision, and surface-roughness, making them ideal for construction and furniture-manufacturing. Therefore, the optimization process, using preheating at 78°C, 16 W laser power, 1.8 m·s−1 scan speed, 0.12 mm scan spacing, and 0.2 mm layer thickness, produced parts with enhanced mechanical strength, surface quality, and dimensional precision, demonstrating their potential for additive manufacturing (AM) applications. This study is one of the first to analyze the impact of SLS parameters on mechanical properties, introducing an innovative SLS material.